THE POSSIBILITIES OF USING AUGMENTED REALITY TECHNOLOGY IN TEACHING ROBOTICS TO SCHOOLCHILDREN - Zhabayev, Ye.; Revshenova, M.; Amangeldin, A. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The article is devoted to exploring the potential of using game elements in teaching robotics within the context of modern STEM education. The use of gamification in the educational process enhances students’ motivation, engagement, and the effectiveness of learning outcomes. An analysis of scientific research has shown that the integration of game mechanics—such as point systems, levels, virtual rewards, and narrative scenarios—has a positive impact on knowledge acquisition, the development of engineering thinking, and the formation of teamwork skills. Special attention is given to the Kazakhstani experience of integrating gamification, particularly through the implementation of the mobile application RoboBil, designed for teaching robotics to middle school students. The application combines theoretical materials, practical tasks, quizzes, and AR-based reward models, enabling personalized learning paths and strengthening the gamification effect. The research results demonstrate that the use of the RoboBil mobile application increases students’ interest in robotics, improves their academic performance, and develops their problem-solving skills. Thus, gamification combined with mobile technologies opens new perspectives for the development of educational robotics and can serve as a model for introducing innovative practices in schools.